Guide to techniques in mouse development - Wassarman, Paul M.; DePamphilis, Melvin L. (Methods in enzymology ;, 1993)
This volume provides, for the first time, an extensive compilation of those state-of-the-art methods that have revolutionized the use of mice as an experimental system. This volume is a unique source for detailed descriptions to be used in research by both experienced and novice researchers - Germ cells and embryos; Fertilization; Gene expression: messenger RNA, reporter genes, proteins, methylation; Gene identification; Nuclear transplantation; Transgenic animals: pronuclear injection, embryonic stem cells, and gene targeting; Lineage analysis. Key Features * Contains the most up-to-date methodology as applied to mouse development * Focuses on molecular approaches to experimental mouse development * The first comprehensive source for molecular biological methods in mouse development * Many of the methods have never appeared before.